Pemikiran Pendidikan Islam Prespektif Buya Hamka - Wahyudin (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The purpose of this study is to determine how Islamic educational thinking according to Buya Hamka, so that it can be applied in the current world of education which is full of problems of inequality of values and morals. The qualitative method used in this study is a literature study that collects books by HAMKA and other books written about HAMKA, as well as literary works in the form of magazines, essays and theses. After that, they are collected, researched and analyzed until a conclusion is obtained. In this study, the author limits his research only to discuss and explore HAMKA's views on education, especially Islamic education in Indonesia. The study shows that Buya Hamka's understanding of Islamic education emphasizes maximum contribution to the development and strengthening of individuals. From the results of this study, the author compiles the process of the birth of HAMKA's thinking so that a connecting line can be seen between HAMKA's educational thinking and his life path. Then the author conducts an analytical study of HAMKA's thinking related to current conditions, so that the author finds the importance of HAMKA's thinking on Islamic education in current conditions, and finally if realized can lead these people to better thinking. better life.